Isolation and identification of microbial species found in cocoa fermentation as microbial starter culture candidates for cocoa bean fermentation in Colombia. - Maria Denis Lozano Tovar; Geraldine Tibasosa; Carlos Mario González; Karen Ballestas Alvarez; Martha del Pilar Lopez Hernandez; Fernando Rodríguez Villamizar (Indonesian Coffee and Cocoa Research Institute, 2020)
Microbial activity involved in the cocoa beans fermentation process is essential to maintain and improve the organoleptic and nutritional qualities of chocolate; therefore, the aim of this investigation was to search and select microbial isolates with the potential to improve the quality of cocoa beans. Fermentation experimentswere conducted on farms located in Maceo (Antioquia), San Vicente de Chucurí (Santander), and Rivera and Algeciras (Huila), Colombia. Yeast, lactic acid bacteria (LAB), acetic acid bacteria (AAB), and mesophilic aerobic microorganisms were obtained from different fermentation batches. The growth of these microorganismswas tested in six treatments as follows: 50% cocoa pulp agar (CPA), high concentrations of glucose (10%), ethanol (5%), and acetic acid (7%), an acidic pH of 3.0, and a high temperature of 50oC for 24 h. The isolates with the highest growth were identified by 18S and 16S rRNA gene analysis, revealing a high diversity ofspecies associated with cocoa fermentation, including eight species of yeasts (Debaryomyces hansenii, Meyerozyma guillermondii, Wickerhanomyces anomalus, Pichia guillermondii, Pichia kudriavzevii, Trichosporon asahii, Candida parapsilosis, and Pichia manshurica), six species of LAB (Pediococcus acidilactici, Lactobacillus brevis, Lactobacillus plantarum, Lactobacillus farraginis, Lactobacillus rhamnosus, and Leuconostoc mesenteroides), four species of AAB (Gluconobacter japonicus, Acetobacter tropicalis, Acetobacter pasteurianus, and Acetobacter malorum/tropicalis), and three species of Bacillus spp. (Bacillusaryabhattai /megaterium, Bacillus subtilis, and Bacillus coagulans). In general, microbial populations increased in cocoa batches after 12 h of fermentation and decreased after 84-96 h. All the yeast isolates grew in 10% glucose and CPA, 85.7% in 5% ethanol, and 95% at a pH of 3.0. All the yeast isolates were affectedby 7% acetic acid and incubation at 50oC for 24 h. Eighty-five percent of the LAB grew in 10% glucose, 100% in 5% ethanol, 42.8% in CPA, 64% at a pH of 3.0, and 35.7% grew after being exposed to 50oC for 24 h; all were affected by 7% acetic acid. As for the AAB, 100% grew in 10% glucose, 71% in 7% ethanol, 100% grew in CPA, in 7% acetic acid, and at a pH of 3.0, while 100% were affected by incubation at 50oC. Three yeast isolates, W. anomalus, D. hansenii and M. guillermondii, three LAB isolates, P. acidilactici, L. brevis, and L. plantarum, and three AAB isolates, A. tropicalis, A. pasteurianus and G. japonicus, were selected as promising strains to be used in a microbial starter culture for cocoa bean fermentation to improve the organoleptic quality of cocoa.